2016
DOI: 10.15406/mojfpt.2016.02.00043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transport Distance on Some Stress Biomarkers Levels in Camel Meat

Abstract: Animals intended for slaughter are subjected to several stress factors which can induce harmful effects on physiological functions as well as the quality of their meat. Road transport is one of the major stressors that affect the well being of the animal. The intensity of the stress depends on several factors, namely the density of the load, the ambient temperature, relative humidity, topography and the distance of transportation. The aim of this investigation was to study the effect of transport distance on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In agreement with our results, El Khasmi et al ( 2010) demonstrated that short-term pre-slaughter transport can lead to a drastic depletion of glycogen in camel muscles. Furthermore, Barka et al (2016) highlighted a significant decrease in glycogen content with an increase in transportation distance. Also, Biffin et al (2020) studied the effect of two different resting times (overnight vs 7 days) on muscle glycogen levels of alpaca (Vicunga pacos) and stated that an extended resting period could induce a significant decrease in glycogen reserves.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In agreement with our results, El Khasmi et al ( 2010) demonstrated that short-term pre-slaughter transport can lead to a drastic depletion of glycogen in camel muscles. Furthermore, Barka et al (2016) highlighted a significant decrease in glycogen content with an increase in transportation distance. Also, Biffin et al (2020) studied the effect of two different resting times (overnight vs 7 days) on muscle glycogen levels of alpaca (Vicunga pacos) and stated that an extended resting period could induce a significant decrease in glycogen reserves.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, it seemed that this short time was not sufficient for a pronounced variation to appear in this trait. In this context, Barka et al (2016) have indicated that the drop in pH was primarily due to the conversion of glycogen into lactic acid and, subsequently, an accumulation of lactate in the muscles. On the other hand, previous study has reported that, due to the presence of humps and their fewer glycolytic enzymes, camels have a high gluconeogenesis capacity, which is characterized by a slower glycolytic pathway compared to other animal species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations